Teaching note-taking in EMI: an experimental study in Economics and Business Administration - Breeze, Ruth; Roothooft, Hanne; Meyer, Marcel (Language learning in higher education (Berlin, Germany), 2024)
Learning to take effective notes is particularly difficult for non-English-native university students enrolled on English Medium Instruction (EMI) courses. However, time and cost constraints mean that many universities provide no support in English for academic purposes or academic skills. One solution to this problem would be to work closely with subject lecturers to develop training that can be delivered within the framework of the EMI content courses themselves. We developed a pilot programme for training students to take effective notes in English and applied it within the context of a first-year content course in Economics and Business Administration at a Spanish university. The students improved on several measures from the pre-test to the post-test, and provided positive feedback. They particularly appreciated learning how to build outlines, simplify information, and use abbreviations and symbols. Questionnaire responses indicated that they had found the training useful and appreciated the possibilities for direct application of the new skills acquired in their other EMI courses. Further research on how to train students in academic language competences within the ecologically valid setting of the EMI classroom itself could include support with subject-focused academic writing and speaking skills.